2022
DOI: 10.1002/adfm.202209249
|View full text |Cite
|
Sign up to set email alerts
|

Holy Water: Photo‐Brightening in Quasi‐2D Perovskite Films under Ambient Enables Highly Performing Light‐Emitting Diodes

Abstract: Quasi‐2D perovskites provide new opportunities for lighting and display applications due to their high radiative recombination and excellent stability. However, seldom attention has been placed on their self‐stability/working operation under ambient storage. Herein, quasi‐2D perovskites/Polyethylene oxide (PEO) films are studied, showing an unforeseen photo‐brightening effect under ambient storage (i.e., an increase of the photoluminescence quantum yield from 55% to 74% after 100 days). In stark contrast, thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…[22][23][24] Additionally, it has been reported that the optical properties and stability of perovskite films in ambient air are significantly affected by light illumination. [25][26][27][28] We thus investigated the stability of these airprocessed blue perovskite films with varying times of light illumination and darkness (Figure S8, Supporting Information). It can be found that in the dark, the films retained their initial PLQY value or PL intensity over 80%; however, when illuminated by white light, they degraded to about 50% of their original values.…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24] Additionally, it has been reported that the optical properties and stability of perovskite films in ambient air are significantly affected by light illumination. [25][26][27][28] We thus investigated the stability of these airprocessed blue perovskite films with varying times of light illumination and darkness (Figure S8, Supporting Information). It can be found that in the dark, the films retained their initial PLQY value or PL intensity over 80%; however, when illuminated by white light, they degraded to about 50% of their original values.…”
Section: Resultsmentioning
confidence: 99%
“…Here, n defines the number of (PbX 6 ) 4– octahedron stacks, where n = ∞ stands for the 3D perovskite . Recently, quasi-2D perovskites have attracted more attention in light-emitting device research due to their strong exciton binding energies and functional cation modification in electroluminescence devices. , The external quantum efficiency has achieved over 25% in red light-emitting devices . However, it has been found that quasi-2D perovskites generate more surface deep defects than 3D perovskites, which could severely influence the radiative recombination process .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] This structure-tunable traits of 2D perovskites are beneficial to control their structural distortion, exciton-phonon coupling and quantum confinement, which in turn, attune their electronic and optical properties. [5][6][7][8][9] Nevertheless, most currently 2D perovskites were synthesized by separating compact 3D structure of traditional ABX 3 (A is cation with large radius, B is cation with smaller radius, X is anion) perovskites with organic cation groups, leading to low purity and mixtures of various layered compounds. [10,11] Different from the 2D perovskites composed of organic spacer molecules, allinorganic A 3 B 2 X 9 perovskites were transformed through replacing divalent B with trivalent cations such as Bi 3+ , showing much higher chemical and structure stability to thermal, moisture and oxidation.…”
Section: Introductionmentioning
confidence: 99%